An Attempt to Gain Gender Equality and Women’s Empowerment In Social Media - Istiqomah, Eri (Universitas Medan Area, 2024)
Social media plays a crucial role in shaping public opinion and crafting narratives around gender issues. The active participation of the community on various social media platforms enriches discussions about gender with diverse perspectives and experiences. Through campaigns, hashtags, and visual content, social media not only provides a space for narratives but also shapes paradigm shifts and social norms related to gender issues. This research aims to identify how the Instagram account @unwomen represents gender equality and women's empowerment issues and explores how @unwomen can influence individuals' perceptions of these issues. The method used is qualitative descriptive with a critical paradigm. Data were collected using a random selection method on posts from the Instagram account @unwomen to provide a fair and representative overview. The posts contain content related to women's rights, employment, closing gender gaps, and the role of women in development. The analysis process involves using critical discourse analysis by Sara Mills, incorporating two concepts: subject-object position and writer-reader position. The analysis includes the identification of text, narratives, and images reflecting gender equality and women's empowerment issues, followed by noting keywords or phrases used in the discourse. Research findings reveal that social media, particularly through the @unwomen account, significantly influences public opinion on gender issues. The subject-object position in gender discourse is reflected in the active role of UN Women as the subject designing messages to influence public opinion as the object. The writer-reader position is reflected in the active role of UN Women as writers responsible for creating messages and content shared using language, images, and specific formats to convey messages and influence the audience. Readers (audience) are individuals or groups consuming and responding to content shared by the @unwomen account. They shape perceptions, interpret messages, and provide feedback. This research integrates Mills' concepts of subject-object and writer-reader positions in the context of social media, highlighting the importance of understanding power dynamics in shaping gender narratives. The results contribute to a deeper understanding of how social media can be used to advocate for gender equality and women's empowerment. Globally, the implications can guide further strategies in addressing gender issues and women's empowerment through social media platforms.